A Clustering Protocol for Data Aggregation in Wireless Sensor Network - Ji Peng; Li Yupeng; Jiang Jingqi; Wang Tianbao (2012 International Conference on Control Engineering and Communication Technology, 2012)
Energy efficiency is one of the most important issues of wireless sensor network (WSN). Since the energy mainly dissipates on data transmission, the data transmission has become the most important issue of WSN recently. Otherwise, the data accuracy is another key factor of data transmission. To optimize these factors, a noble routing protocol is proposed in this paper. The proposed algorithm is originated from LEACH, and energy efficiency and latency is considered as the researching parameters. The overlap of detect regions is discussed and a nodes-adaptive schedule is designed to reduce the amount of data with LEACH protocol. Moreover, a data aggregation is also studied, which takes the data aggregate along the transmission process. The proposed protocol is evaluated in comparison with the traditional LEACH, and the performance of the proposed protocol is verified to be efficient and competent.